2003
DOI: 10.1038/sj.bmt.1704226
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model of peripheral blood stem cell harvest kinetics

Abstract: Summary:A mathematical model of peripheral blood stem cell harvests was developed, taking two new parameters R (number of recruited cells/minute) and E f (efficiency of collection) into consideration in addition to concentrations and collected amounts of cells. This model was tested on 241 harvest procedures in cancer patients (chemotherapy þ G-CSF stimulation), donors of allogeneic PBSC, and platelet donors, using different collection procedures, with a Cobe Spectra Cell separator. The relationships between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…Several studies have concluded to the presence of intra‐apheresis CD34+ cell recruitment into the blood ; however, this recruitment phenomenon has not always been reported . Mayer et al developed a mathematical model of peripheral blood stem cell harvests which demonstrated that recruitment played an important role and contributed significantly to the final harvest . However, recruitment was significantly influenced by pre‐treatment with chemotherapy and/or radiotherapy with much lower values for patients with moderate and extensive pretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have concluded to the presence of intra‐apheresis CD34+ cell recruitment into the blood ; however, this recruitment phenomenon has not always been reported . Mayer et al developed a mathematical model of peripheral blood stem cell harvests which demonstrated that recruitment played an important role and contributed significantly to the final harvest . However, recruitment was significantly influenced by pre‐treatment with chemotherapy and/or radiotherapy with much lower values for patients with moderate and extensive pretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…As we are showing, a greater stem cell yield and significantly lower PLT reinfusion rate were achieved 9‐11 . These tangible advantages must be balanced against a higher contamination with granulocytes and granulocytic precursors in Spectra Optia v.5.0 apheresis products, which, however, remained markedly below numbers reported for alternative apheresis systems 7,12‐15 .…”
mentioning
confidence: 83%
“…As a result, the number of circulating WBCs is much lower in MNC collection, resulting in a thinner layer of WBCs (also known as buffy coat). Second, the circulating MNCs decrease more rapidly during collection as compared to HPC collection because of a lack of active MNC replenishment from bone marrow mobilization . Moreover, the procedure time and processed blood volume for collection of MNCs is usually shorter or less than that of HPC collections because fewer MNCs are typically required.…”
mentioning
confidence: 99%